To What Extent is Demonstration-Based Instruction Effective in Music Education? - Sembiring, Piter (Yayasan Cendekiawan Indonesia Timur, 2026)
This study analyzes demonstration-based instruction in music education through an integrative review of twenty peer-reviewed studies published between 2019 and 2026. The review employs an integrative synthesis approach involving systematic literature search across Google Scholar, SINTA, and Scopus, followed by screening based on predefined inclusion and exclusion criteria and thematic comparative analysis of quantitative, qualitative, and mixed-methods studies. The synthesis shows that demonstration supports learning outcomes, including psychomotor development, technical proficiency, coordination, musical literacy, and interpretative performance across instrumental and vocal contexts. However, its effectiveness varies depending on instructional design and is significantly strengthened when combined with active learning strategies, goal-oriented instruction, and performance-based assessment. The study proposes an integrative pedagogical framework that positions demonstration as foundational modeling within a structured sequence of exploration and evaluation. Rather than functioning as an isolated practice, demonstration is conceptualized as a core component within a coherent instructional system. This study contributes to the literature by synthesizing fragmented findings into a unified analytical perspective that clarifies the conditions under which demonstration-based instruction is most effective in music education.